(untitled) (Collection of scientific works «Modern structures of metal and wood», 2022)
One of the modern ways to increase the bearing capacity of the walls of metal cylindrical structures that perceive the action of internal pressure is the external transversely directed reinforcement by fiber reinforced plastics (FRP), the most effective type of which is made from carbon fibers (CFRP). Consideration of metal cylindrical shells, which perceive the action of internal pressure and are reinforced with external transversely directed FRP reinforcement, makes it possible to obtain the values of the stress state parameters of the corresponding structures. At the same time, analytical methods for estimating these parameters do not have the necessary experimental justification. In this connection, experimental studies of the stress state of elements of models of metal cylindrical structures externally reinforced with transversely directed FRP based on high strength and high modulus carbon fibers were carried out. The results of tests, including taking into account variable operating temperatures, are presented in this paper in comparison with the conclusions of the previously proposed practical methods of the corresponding analytical assessment. The paper substantiates the applicability of applied analytical methods for determining the parameters of the stress state in the elastic stage of deformation of the elements of the complex walls of metal cylindrical shells externally reinforced with transversely directed FRP elements made on the basis of normal modulus and high modulus carbon fibers.